Demographic policy of Latvia: problems and prospects - Tsaurkubule, Zhanna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The article examines the effects of influence of demographic policy on the formation and development of human resources in Latvia. The objective of the article aims to determine “weak points” of population system’s policy and develop the conceptual proposals that will resolve existing disputes. The main indicators characterizing a demographic situation in Latvia are analysed. The results of the analysis indicate the existence of deep demographic crisis in Latvia. Without taking effective measures to improve the demographic situation, the population of Latvia will decrease dramatically. In the conclusion, the proposals on the increasing the effectiveness of the system of demographic policy in Latvia were put forward
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 465, s. 156-165
Keywords: Latvia; demographic situation; demographic policy; indicators; demographic crisis; Łotwa; sytuacja demograficzna; polityka demograficzna; wskaźniki